Longitudinal computational fluid dynamics study of aneurysmal dilatation in a chronic DeBakey type III aortic dissection - Karmonik, Christof; Partovi, Sasan; Müller-Eschner, Matthias; Böckler, Dittmar; Tengg-Kobligk, Hendrik von (Journal of vascular surgery, 2012)
Computational fluid dynamics, which uses numeric methods and algorithms for the simulation of blood flow by solving the Navier-Stokes equations on computational meshes, is enhancing the understanding of disease progression in type III aortic dissections. To illustrate this, we examined the changes in patient-derived geometries of aortic dissections, which showed progressive false lumen aneurysmal dilatation (26% diameter increase) during follow-up. Total pressure was decreased by 29% during systole and by 34% during retrograde flow. At the site of the highest false lumen dilatation, the temporal average of total pressure decreased from 45 to 22 Pa, and maximal average wall shear stress decreased from 0.9 to 0.4 Pa. These first results in the study of disease progression of type III DeBakey aortic dissection with computational fluid dynamics are encouraging.
Available online 9 May 2012
Gesehen am 28.06.2018